INTEGRATING DIGITAL TOOLS IN TEACHER EDUCATION: A WORKSHOP ON WEBSITE DEVELOPMENT FOR FILIPINO PRE-SERVICE TEACHERS - Delina, Mutia; Magno, Ricky M; Muhasyah, Surano (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Universitas Negeri Jakarta (UNJ) conducted international workshop aimed at enhancing the ICT literacy of Filipino pre-service teachers through practical website development training. The workshop was attended by 17 pedagogical students from six higher education institutions in the Philippines, divided into two batches in February and March 2025. Guided by a facilitator from UNJ, the participants were trained to use Weebly, a user-friendly website platform, to create educational websites without requiring programming skills. These websites incorporated essential instructional elements, including lesson plans, multimedia teaching materials, interactive learning exercises, assessments, and evaluation tools. The project emphasized the integration of digital technology in teaching and learning, equipping future educators with the skills necessary for 21st-century classrooms. Participants later presented their websites in October 2025, demonstrating how they applied these platforms in their teaching practice. This initiative highlights the critical role of teacher education institutions in bridging the ICT literacy gap and preparing future teachers for digital transformation in education.